2018
DOI: 10.3390/ma11050779
|View full text |Cite
|
Sign up to set email alerts
|

Drug Delivery Nanosystems for the Localized Treatment of Glioblastoma Multiforme

Abstract: Glioblastoma multiforme is one of the most prevalent and malignant forms of central nervous system tumors. The treatment of glioblastoma remains a great challenge due to its location in the intracranial space and the presence of the blood–brain tumor barrier. There is an urgent need to develop novel therapy approaches for this tumor, to improve the clinical outcomes, and to reduce the rate of recurrence and adverse effects associated with present options. The formulation of therapeutic agents in nanostructures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 143 publications
(151 reference statements)
0
54
0
1
Order By: Relevance
“…Since the local administration of drugs has been investigated as it offers the possibility to bypass the BBB and blood brain tumor barrier (BBTB), concentrating higher amounts of drug in malignant tumors (Nam et al, 2018), it would be interesting to provide a locally sensitive strategy which would make it possible to have synergism with other actions including radiotherapy for the cleavage and drug activity. For the moment, pilot clinical studies using intravenous MPH have not shown any significant impact (Anderson et al, 2015).…”
Section: Evaluation Of the Potential Synergistic Effect Of X-ray Irramentioning
confidence: 99%
“…Since the local administration of drugs has been investigated as it offers the possibility to bypass the BBB and blood brain tumor barrier (BBTB), concentrating higher amounts of drug in malignant tumors (Nam et al, 2018), it would be interesting to provide a locally sensitive strategy which would make it possible to have synergism with other actions including radiotherapy for the cleavage and drug activity. For the moment, pilot clinical studies using intravenous MPH have not shown any significant impact (Anderson et al, 2015).…”
Section: Evaluation Of the Potential Synergistic Effect Of X-ray Irramentioning
confidence: 99%
“…The cytotoxicity of the magnetic microdiscs was assessed by the standard 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay (Abcam ab211091, Cambridge, UK). T98G cells were plated into 96 well plates (8000 cells per well) for 24 h. Then different concentrations of microdiscs (10,20,30,40 and 50 ND per cell) were added, the cells were cultured for another day.…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%
“…To further improve tumor accumulation, an active targeting moiety, such as hyaluronic acid or folic acid, could be incorporated into the micelle design to target receptors overexpressed on GBM cells (ie CD44 and folate, respectively). 48,49 These ligands can be conjugated to the micelle surface in efforts to improve the chemotherapeutic impact and translational potential of these micelles.…”
Section: Pharmacokinetics and Biodistribution In Ectopic Mouse Xenogrmentioning
confidence: 99%